Diamond-like protective coating as well as preparation method and application thereof
The diamond-like protective coating is prepared at room temperature by plasma gas phase physical deposition method, which solves the problem of thermal damage to flexible polymer substrates caused by high temperature deposition of existing DLC coatings, and achieves coatings with high hardness, low friction coefficient and high light transmittance, extending the service life of the material.
Patent Information
- Application Number
- CN202510065897.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing diamond-like (DLC) coatings are prepared by chemical vapor deposition (CVD) methods and need to be carried out under high temperature conditions, resulting in irreversible thermal damage to the flexible polymer substrate and reducing its mechanical properties and appearance quality.
The diamond-like protective coating is prepared under normal temperature conditions by using plasma gas phase physical deposition method. By adjusting the target base distance, vacuum degree, ion source voltage, carbon source gas flow rate and deposition time, a coating with good mechanical properties is formed.
While maintaining the excellent wear resistance and light transmittance of diamond-like coatings, it significantly improves the hardness and elastic modulus of flexible polymer substrates, extends its service life, and avoids damage to the substrate by high-temperature treatment.
Smart Images

Figure CN119843223A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hard films, and in particular relates to a diamond-like protective coating and a preparation method and application thereof. Background Art
[0002] In the field of modern microelectronics, flexible polymer materials are widely used in flexible electronic devices, sensors, displays and wearable devices due to their excellent electrical properties, lightweight characteristics and good processability. However, these materials usually have low hardness and their surfaces are easily damaged and fail due to mechanical damage and wear, which affects their long-term stability and service life. Especially in the process of micro-nano processing and manufacturing, due to the significant adhesion effect and low wear resistance on the surface of polymer materials, the problem of friction damage is more prominent. Therefore, improving the wear resistance of the surface of flexible polymer materials has become a technical problem that urgently needs to be solved.
[0003] At present, the research focus of friction protection technology for flexible polymer substrates is mainly on improving material performance through surface coatings; among them, diamond-like carbon (DLC) coatings have become an ideal protective coating due to their high hardness, low friction coefficient and excellent wear resistance. However, existing DLC coatings are mainly prepared by chemical vapor deposition (CVD) methods, which require high temperature conditions, which will cause irreversible thermal damage to flexible polymer substrates (such as polyethylene terephthalate, PET), significantly reducing their mechanical properties and appearance quality.
[0004] In order to solve this technical bottleneck, a process for preparing DLC coating at room temperature was developed, which can not only maintain the excellent wear resistance of DLC coating, but also ensure the mechanical properties of polymer substrate, which is of great significance to the reliability and service life of flexible electronic devices. Summary of the invention
[0005] In view of this, the present invention provides a diamond-like protective coating and a preparation method and application thereof. The method provided by the present invention can prepare a diamond-like protective coating with good mechanical properties at room temperature.
[0006] In order to solve the above technical problems, the present invention provides a method for preparing a diamond-like protective coating, comprising the following steps:
[0007] Plasma vapor phase physical deposition is performed on the surface of a flexible polymer substrate to form a diamond-like protective coating;
[0008] The conditions of the plasma gas phase physical deposition include: a target-substrate distance of 15 to 50 cm, a vacuum degree of 0.1 to 10 Pa, an ion source voltage of 50 to 500 V, an ion source current of 0.5 to 10 A, a deposition time of 10 to 1200 s, a flow rate of the carbon source gas of 50 to 500 sccm, a duty cycle of 10 to 90%, and a deposition temperature of 10 to 25° C.
[0009] Preferably, the conditions of the plasma vapor phase physical deposition include: a target-substrate distance of 16.6 to 18.6 cm, a vacuum degree of 0.2 to 3 Pa, an ion source voltage of 310 to 490 V, an ion source current of 2.5 to 5 A, a deposition time of 30 to 300 s, a flow rate of the carbon source gas of 150 to 250 sccm, a duty cycle of 50 to 80%, and a deposition temperature of 10 to 25°C.
[0010] Preferably, the flexible polymer substrate comprises polymethyl methacrylate, polyethyl methacrylate, polyethylene terephthalate, polycyclohexyl dimethyl terephthalate, polyether ketone, polyether imide, polyethylene or polycyclopentadiene.
[0011] Preferably, the carbon source gas includes methane, propane or acetylene.
[0012] Preferably, before the plasma vapor phase physical deposition, the method further comprises: cleaning and drying the flexible polymer substrate.
[0013] Preferably, the cleaning comprises sequentially washing with water and washing with an organic solvent;
[0014] The organic solvent used for the organic solvent washing includes petroleum ether or ethanol. The organic solvent washing is performed under ultrasonic conditions, and the ultrasonic time is 10 to 15 minutes.
[0015] Preferably, the drying temperature is 30-40° C. and the drying time is 5-8 hours.
[0016] The present invention also provides a diamond-like protective coating prepared according to the preparation method described in the above technical scheme, wherein the diamond-like protective coating has a thickness of 10 to 100 nm, a hardness of 25,000 to 42,000 MPa, an elastic modulus of 95 to 120 GPa, a friction coefficient of 0.05 to 0.1, and a light transmittance of more than 80%.
[0017] Preferably, the diamond-like protective coating has a thickness of 15.3 to 50.6 nm, a hardness of 26184.17 to 41286.61 MPa, an elastic modulus of 96.29 to 112.78 GPa, a friction coefficient of 0.073 to 0.085, and a light transmittance of 81.9 to 90.3%.
[0018] The present invention also provides the application of the diamond-like protective coating described in the above technical solution in the field of protection of micro-flexible electronic devices.
[0019] The present invention provides a method for preparing a diamond-like protective coating, comprising the following steps: performing plasma vapor phase physical deposition on the surface of a flexible polymer substrate to form a diamond-like protective coating; the conditions of the plasma vapor phase physical deposition include: a target-substrate distance of 15 to 50 cm, a vacuum degree of 0.1 to 10 Pa, an ion source voltage of 50 to 500 V, an ion source current of 0.5 to 10 A, a deposition time of 10 to 1200 s, a carbon source gas flow rate of 50 to 500 sccm, a duty cycle of 10 to 90%, and a deposition temperature of 10 to 25° C. The present invention performs plasma vapor phase physical deposition at a relatively low temperature under specific conditions, and the prepared diamond-like protective coating has both good mechanical properties and light transmittance, and can be used for micro flexible electronic devices to improve their reliability and service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The SEM images of the diamond-like coatings prepared in Examples 1, 2, 5 and 6, wherein a is the SEM image of Example 1, b is the SEM image of Example 2, c is the SEM image of Example 5, and d is the SEM image of Example 6;
[0021] Figure 2 The light transmittance results of the coatings of Examples 1 to 4 and Comparative Example 2 are shown;
[0022] Figure 3 It is a columnar comparison chart of the hardness of the coatings of Examples 1 to 4 and Comparative Example 2 obtained through nanoindentation experiments;
[0023] Figure 4 It is a columnar comparison chart of elastic modulus obtained by nanoindentation test of the coatings of Examples 1, 2, 5, 6 and Comparative Example 2;
[0024] Figure 5 This is a columnar comparison chart of friction dilution obtained by nanoindentation test of the coatings of Examples 1, 2, 5, 6 and Comparative Example 2;
[0025] Figure 6 These are AFM morphology images after nano friction and wear tests were carried out on the surfaces of Example 1 and the polyethylene terephthalate substrate (Comparative Example 2) using AFM; wherein a is a morphology image of Example 1 with a friction cycle of 1000 cycles under a load of 1 μN, b is a morphology image of Example 1 with a friction cycle of 1000 cycles under a load of 20 μN, and c is a morphology image of Comparative Example 2 with a friction cycle of 1000 cycles under a load of 1 μN. DETAILED DESCRIPTION
[0026] The present invention provides a method for preparing a diamond-like protective coating, comprising the following steps:
[0027] Plasma vapor phase physical deposition is performed on the surface of a flexible polymer substrate to form a diamond-like protective coating;
[0028] The conditions of the plasma gas phase physical deposition include: a target-substrate distance of 15 to 50 cm, a vacuum degree of 0.1 to 10 Pa, an ion source voltage of 50 to 500 V, an ion source current of 0.5 to 10 A, a deposition time of 10 to 1200 s, a flow rate of the carbon source gas of 50 to 500 sccm, a duty cycle of 10 to 90%, and a deposition temperature of 10 to 25° C.
[0029] As a specific embodiment of the present invention, the flexible polymer substrate may include polymethyl methacrylate, polyethyl methacrylate, polyethylene terephthalate, polycyclohexyl dimethyl terephthalate, polyether ketone, polyetherimide, polyethylene or polycyclopentadiene; the thickness of the flexible polymer substrate may be 1-5 μm, or 2-4 μm. As a specific embodiment of the present invention, the process before plasma vapor phase physical deposition may also include: cleaning and drying the flexible polymer substrate; the cleaning may include sequential water washing and organic solvent washing; the water used for the water washing may be deionized water; the organic solvent used for the organic solvent washing may include petroleum ether or ethanol, the organic solvent washing may be carried out under ultrasonic conditions, and the ultrasonic time may be 10-15 minutes. As a specific embodiment of the present invention, the drying temperature may be 30-40°C, or 60-70°C; the drying time may be 5-8h, or 6-7h.
[0030] As a specific embodiment of the present invention, the carbon source gas may include methane, propane or acetylene.
[0031] As a specific embodiment of the present invention, the plasma vapor phase physical deposition may also include: after cleaning the tube furnace, installing the cleaned flexible polymer substrate on the workpiece rack, evacuating the tube furnace, introducing inert gas to physically clean the flexible polymer substrate, extracting the residual gas in the vacuum chamber, and turning on the ion source. The present invention has no special requirements for the method of cleaning the tube furnace and installing the flexible polymer substrate, and conventional methods in the art can be used. As a specific embodiment of the present invention, the vacuum degree of the tube furnace can be (3 to 5) × 10 -3 Pa, can also be (3.5~4)×10 -3Pa; the inert gas can be argon gas, and the purity of the argon gas is above 99.9%; the flow rate of the inert gas can be 500-900sccm, and can also be 600-800sccm; the physical cleaning can be glow cleaning, and the negative bias voltage of the glow cleaning can be -700-850V, and can also be -750-800V, and the time of the glow cleaning can be 10-30min, and can also be 15-25min.
[0032] As a specific embodiment of the present invention, the conditions of the plasma gas phase physical deposition include: a target-substrate distance of 15 to 50 cm, a vacuum degree of 0.1 to 10 Pa, an ion source voltage of 50 to 500 V, an ion source current of 0.5 to 10 A, a deposition time of 10 to 1200 s, a flow rate of a carbon source gas of 50 to 500 sccm, a duty cycle of 10 to 90%, and a deposition temperature of 10 to 25° C.; the conditions of the plasma gas phase physical deposition may also include: a target-substrate distance of 16.6 to 18.6 cm, a vacuum degree of 0.2 to 3 Pa, an ion source voltage of 310 to 490 V, an ion source current of 2.5 to 5 A, a deposition time of 30 to 300 s, a flow rate of a carbon source gas of 150 to 250 sccm, a duty cycle of 50 to 80%, and a deposition temperature of 10 to 25° C.; the target-substrate distance is the vertical distance between the linear plasma source and the workpiece holder in the chamber.
[0033] The present invention performs plasma vapor phase physical deposition under specific conditions to obtain a protective coating with good mechanical properties, good light transmittance and good wear resistance; the change of deposition distance (target-substrate distance) will affect the structure of the coating, and as the deposition distance increases, the coating structure may change from a dense layered structure to a quasi-columnar structure with more particles, and then to an EB-PVD-like columnar structure, and finally to a quasi-nanoscale columnar structure with a smooth surface and large gaps between columns; the vacuum degree affects the stability of the plasma and the purity of the coating, and a higher vacuum degree helps to form a more stable plasma and reduce the collision of gas molecules, thereby possibly improving the uniformity and purity of the coating; the ion source voltage affects the energy and deposition rate of the ions, and a higher voltage will increase the energy of the ions and increase the ionization rate, thereby possibly increasing the deposition rate and the hardness of the coating; the ion source current affects the density of the plasma and the deposition rate of the coating, and a larger current will increase the density of the plasma, which may Increase the deposition rate, but too high current may cause damage to the coating structure; deposition time affects the thickness and uniformity of the coating. Longer deposition time can increase the thickness of the coating, but it may also affect the microstructure and properties of the coating, such as hardness and friction coefficient; gas flow rate affects the growth rate and chemical composition of the coating. Higher gas flow rate can increase the growth rate of the coating, but it may also affect the chemical structure of the coating, thereby affecting its hardness and chemical stability; changes in duty cycle will affect the stability and uniformity of plasma discharge. When the duty cycle decreases, the bulk plasma density becomes lower because energy absorption is limited during the shorter active glow period, which means that a lower duty cycle may lead to an uneven distribution of plasma density, affecting the quality and performance of the coating; deposition temperature affects the structure and adhesion of the coating. A lower deposition temperature helps to maintain the dimensional stability of the substrate material and reduce thermal stress, while helping to improve the adhesion of the coating and reduce internal stress.
[0034] The preparation method provided by the present invention does not require a heat source to provide energy and can be carried out at room temperature; the DLC protective coating prepared by the plasma vapor phase physical deposition method adopted by the present invention has good density and mechanical properties, and can significantly improve the hardness and elastic modulus of the substrate. The hardness and elastic modulus of the substrate with a DLC coating on the surface are about 100 times or more of that of the substrate without a protective coating; the DLC coating prepared by the present invention exhibits excellent protective effects at the nanoscale. Under the same test conditions, compared with the polymer substrate without a protective coating, it is extremely difficult for the probe to wear on the surface of the DLC coating; under the same friction cycle, the contact stress between the probe and the DLC coating surface is increased to more than 10 times that of the polymer substrate to produce nanoscale wear, which shows that the DLC coating can effectively protect the surface of the polymer substrate, so that it maintains high integrity and mechanical properties during the nano-friction process. The diamond-like coating prepared on the surface of the flexible material according to the preparation method provided by the present invention contains a sp ratio of 3:2. 3 and sp2 Carbon bonds can maintain a low friction coefficient under the application requirements of low thickness and high transmittance, and its transmittance is not less than 80%.
[0035] The present invention deposits a diamond-like coating on the surface of a flexible polymer material by a plasma gas phase physical deposition method, which has a very low effect on the light transmittance of the substrate. The present invention prepares a diamond-like coating in a carbon source gas, which has good tribological and mechanical properties, can form a dense hard coating on the surface of the flexible polymer, and significantly improves the wear resistance and mechanical properties of the flexible polymer substrate, thereby extending its service life.
[0036] The present invention also provides a diamond-like protective coating prepared by the preparation method described in the above technical scheme, wherein the thickness of the diamond-like protective coating is 10 to 100 nm, and can be 15.3 to 50.6 nm; the hardness of the diamond-like protective coating is 25000 to 42000 MPa, and can be 26184.17 to 41286.61 MPa; the elastic modulus of the diamond-like protective coating is 95 to 120 GPa, and can be 96.29 to 112.78 GPa; the friction coefficient of the diamond-like protective coating is 0.05 to 0.1, and can be 0.073 to 0.085; the light transmittance of the diamond-like protective coating is above 80%, and can be 81.9 to 90.3%.
[0037] The present invention also provides an application of the diamond-like protective coating described in the above technical solution in the field of protection of micro flexible electronic devices. As a specific embodiment of the present invention, the micro flexible electronic device includes an electronic device in a flexible display screen, a wearable device, a flexible solar cell or a flexible circuit board.
[0038] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0039] Example 1
[0040] Polyethylene terephthalate was selected as the flexible polymer substrate and cut into 10 cm × 10 cm × 50 μm sheets; the polyethylene terephthalate sheets were washed with deionized water and then ultrasonically cleaned in petroleum ether for 15 min, then placed in a vacuum drying oven at 60 ° C for 6 h, taken out and placed in the workpiece holder in the cavity, and the target-substrate distance was adjusted to 18.6 cm;
[0041] Before deposition, the air in the chamber was evacuated to make the chamber reach a vacuum state. The vacuum degree in the vacuum state was 3×10 -3Pa; argon gas with a purity of 99.9% was introduced into the vacuum chamber for glow cleaning, the argon gas flow rate was 600 sccm, the negative bias voltage of glow cleaning was -800 V, and the glow cleaning time was 25 min; the argon gas was turned off and the vacuum degree was readjusted to 3×10 -3 Pa, adjust the ion source voltage to 310V and the current to 2.5A, then introduce acetylene for plasma vapor phase physical deposition. The vacuum degree of plasma vapor phase physical deposition is 0.4Pa, the acetylene gas flow rate is 150sccm, the duty cycle is 50%, the temperature is 20°C, and the deposition time is 30s to obtain a diamond-like coating with a thickness of 15.3nm, which is recorded as M1.
[0042] Example 2
[0043] The diamond-like coating was prepared according to the method of Example 1, except that the deposition time was 90 s, and the thickness of the prepared diamond-like coating was 33.8 nm, which was recorded as M2.
[0044] Example 3
[0045] The diamond-like coating was prepared according to the method of Example 1, except that the deposition time was 150 s, and the thickness of the prepared diamond-like coating was 39.2 nm, which was recorded as M3.
[0046] Example 4
[0047] The diamond-like coating was prepared according to the method of Example 1, except that the deposition time was 210 s, and the thickness of the prepared diamond-like coating was 44.9 nm, which was recorded as M4.
[0048] Example 5
[0049] The diamond-like coating was prepared according to the method of Example 1, except that the ion source voltage was 400 V and the acetylene gas flow rate was 250 sccm. The thickness of the prepared diamond-like coating was 43.1 nm, which was recorded as C1.
[0050] Example 6
[0051] The diamond-like coating was prepared according to the method of Example 1, except that the ion source voltage was 490 V and the acetylene gas flow rate was 250 sccm. The thickness of the prepared diamond-like coating was 50.6 nm, which was recorded as C2.
[0052] Comparative Example 1
[0053] The diamond-like coating was prepared according to the method of Example 2, except that the acetylene gas flow rate was 550 sccm, and the thickness of the prepared diamond-like coating was 76.3 nm.
[0054] Comparative Example 2
[0055] Polyethylene terephthalate was used as a comparative example and was denoted as PET.
[0056] The diamond-like coatings prepared in Examples 1, 2, 5 and 6 were observed using a scanning electron microscope to obtain SEM images. Figure 1 As shown, a is the SEM image of Example 1, b is the SEM image of Example 2, c is the SEM image of Example 5, and d is the SEM image of Example 6. Figure 1 It can be seen that the thickness of the diamond-like coating can be controlled by adjusting the deposition time and gas flow rate.
[0057] The transmittance of the coatings of Examples 1 to 4 and Comparative Examples 1 to 2 was measured by UV-visible spectrophotometer, and the result graphs of Examples 1 to 4 and Comparative Example 2 were obtained, as shown in FIG. Figure 2 shown.
[0058] Nano friction and wear tests and nano indentation tests were carried out using an atomic force microscope (AFM) to study the effect of diamond-like carbon (DLC) coating on the mechanical and tribological properties of polymer substrates at the nanoscale. The results are listed in Table 1. The nano friction and wear test was carried out at room temperature (25°C), the load applied by the probe was 1 μN, the friction cycle was 100 times, and the friction coefficient was obtained. After the test, AFM was used to collect in-situ morphological data. The nano indentation test was also carried out at room temperature (25°C), the probe loading force was 10 μN, 20 μN, 40 μN, and 80 μN. After the test, AFM was also used to collect in-situ morphological data, and the indentation depth and width were recorded for calculating the hardness and elastic modulus.
[0059] Table 1 Mechanical properties of the coatings prepared in Examples 1 to 6 and Comparative Examples 1 to 2
[0060]
[0061]
[0062] Combining Table 1 and Figure 2 It can be seen that as the deposition time increases, the coating thickness of Examples 1 to 4 increases continuously. Since the DLC coating itself has optical opacity, the light transmittance of the material decreases continuously. When the coating thickness is 50.6 nm, the minimum light transmittance is 81.9%. Moreover, it decreases by about 8.5% compared with the substrate without coating, indicating that the DLC coating prepared on the surface of the polymer substrate by the method of the present invention can still maintain good light transmittance.
[0063] According to Table 1, a columnar comparison chart of the hardness of the coatings of Examples 1 to 4 and Comparative Example 2 obtained by nanoindentation test is drawn, as shown in FIG. Figure 3As shown; according to Table 1, a columnar comparison chart of the elastic modulus obtained by nanoindentation test of the coatings of Examples 1, 2, 5, 6 and Comparative Example 2 is drawn, as shown Figure 4 As shown; according to Table 1, a columnar comparison chart of friction dilution obtained by nanoindentation experiment of the coatings of Examples 1, 2, 5, 6 and Comparative Example 2 is drawn, as shown Figure 5 As shown. Figures 3 to 5 It can be seen that the DLC coating prepared by the present invention can significantly improve the hardness and elastic modulus of the polymer substrate, providing a good protective effect for it, and its hardness and elastic modulus are about 100 times more than that of the polymer substrate. At the same time, the hardness and elastic modulus of the coatings prepared in each embodiment are not much different, indicating that the DLC coating prepared by the present invention has good stability and consistency.
[0064] The materials of Example 1 and Comparative Example 2 were subjected to nano-removal experimental tests, and the condition parameters included: 1000 cycles, loads of 20 μN and 1 μN, and friction speeds of 10 μm / s. Figure 6 The AFM morphology images after the nano-removal test on the surface of Example 1 and the polyethylene terephthalate substrate (Comparative Example 2) using AFM. a is the morphology image of Example 1 with a friction cycle of 1000 cycles under a load of 1μN, b is the morphology image of Example 1 with a friction cycle of 1000 cycles under a load of 20μN, and c is the morphology image of Comparative Example 2 with a friction cycle of 1000 cycles under a load of 1μN. Figure 6 It can be seen that, compared with the PET substrate without protective coating, Example 1 with DLC coating shows extremely strong wear resistance under the same friction cycle. Under the same friction cycle, the contact stress between the probe and the DLC coating surface needs to be increased to more than 10 times that of the polymer substrate to produce nano-level wear. At this time, the wear scar depth of the DLC coating surface is about 1nm, which is only 1% of the polymer substrate. This shows that the DLC coating can effectively protect the surface of the polymer substrate during nano-wear and play a good protective role.
[0065] The preparation method provided by the present invention can realize the deposition of high-quality DLC coating on a flexible substrate under room temperature conditions, thereby solving the problem of thermal damage to the flexible material caused by high-temperature deposition; and the prepared DLC coating can not only improve the wear resistance and mechanical properties of the substrate, but also ensure that the substrate still has good light transmittance after being coated. This is because DLC is a sp 2 (graphitic carbon) and sp 3 (diamond carbon) bond mixture composed of amorphous materials, in which sp 3 The regulation of the bond ratio is crucial to the optical properties of the material. 3The bond content makes it have a lower light absorption coefficient, thereby improving the light transmittance. At the same time, due to the uniformity of the amorphous structure, the DLC coating can reduce the scattering effect of light in the coating, which helps to improve the light transmittance. 2 The reasonable distribution of bonds can optimize the optical band gap of the material and reduce the light absorption in the visible light range, making it have a wider application prospect in the application field of flexible electronic devices.
[0066] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a diamond-like protective coating, characterized in that: The following steps are involved: Plasma vapor phase physical deposition is performed on the surface of a flexible polymer substrate to form a diamond-like protective coating; The conditions of the plasma gas phase physical deposition include: a target-substrate distance of 15 to 50 cm, a vacuum degree of 0.1 to 10 Pa, an ion source voltage of 50 to 500 V, an ion source current of 0.5 to 10 A, a deposition time of 10 to 1200 s, a flow rate of the carbon source gas of 50 to 500 sccm, a duty cycle of 10 to 90%, and a deposition temperature of 10 to 25° C.
2. The preparation method according to claim 1, characterized in that: The conditions of the plasma gas phase physical deposition include: a target-substrate distance of 16.6 to 18.6 cm, a vacuum degree of 0.2 to 3 Pa, an ion source voltage of 310 to 490 V, an ion source current of 2.5 to 5 A, a deposition time of 30 to 300 s, a flow rate of the carbon source gas of 150 to 250 sccm, a duty cycle of 50 to 80%, and a deposition temperature of 10 to 25° C.
3. The preparation method according to claim 1, characterized in that: The flexible polymer substrate includes polymethyl methacrylate, polyethyl methacrylate, polyethylene terephthalate, polycyclohexyl dimethyl terephthalate, polyether ketone, polyether imide, polyethylene or polycyclopentadiene.
4. The preparation method according to claim 1, characterized in that: The carbon source gas includes methane, propane or acetylene.
5. The preparation method according to claim 1, characterized in that: Before the plasma vapor phase physical deposition is performed, the method further comprises: cleaning and drying the flexible polymer substrate.
6. The preparation method according to claim 5, characterized in that: The cleaning comprises sequentially washing with water and washing with an organic solvent; The organic solvent used for the organic solvent washing includes petroleum ether or ethanol. The organic solvent washing is performed under ultrasonic conditions, and the ultrasonic time is 10 to 15 minutes.
7. The preparation method according to claim 5, characterized in that: The drying temperature is 30-40° C. and the drying time is 5-8 hours.
8. The diamond-like protective coating prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The diamond-like protective coating has a thickness of 10 to 100 nm, a hardness of 25,000 to 42,000 MPa, an elastic modulus of 95 to 120 GPa, a friction coefficient of 0.05 to 0.1, and a light transmittance of more than 80%.
9. The diamond-like protective coating according to claim 8, characterized in that: The diamond-like protective coating has a thickness of 15.3 to 50.6 nm, a hardness of 26184.17 to 41286.61 MPa, an elastic modulus of 96.29 to 112.78 GPa, a friction coefficient of 0.073 to 0.085, and a light transmittance of 81.9 to 90.3%.
10. Application of the diamond-like protective coating according to claim 8 or 9 in the field of protection of micro flexible electronic devices.
Citation Information
Patent Citations
Preparation method of transparent hydrophobic abrasion-resistant diamond-like film on transparent polymer surface
CN105861990A
Diamond-like moisture-resistant coating on surface of flexible packaging material as well as preparation method and application of diamond-like moisture-resistant coating
CN117070925A
High thermal conductive and high air-tightness packaging material of film and preparation method
CN1563243A